Are recommended dosages of copper-based Marine Growth Prevention Systems (MGPS) effective for vessel biosecurity? - Bailey Lovett; Patrick Cahill; Javier Atalah; Julien Vignier; Lauren Fletcher; Juliette Butler; Hannah Appleton; Olivier Champeau; Matthew Reardon; Eugene Georgiades; Yasmin Gabay; Daniel Kluza; et al. (Marine Pollution Bulletin, 2025)

Fatty acid production and associated gene pathways are altered by increased salinity and dimethyl sulfoxide treatments during cryopreservation of Symbiodinium pilosum (Symbiodiniaceae) - Joseph K. Kihika; John K. Pearman; Susanna A. Wood; Lesley L. Rhodes; Kirsty F. Smith; Matthew R. Miller; Juliette Butler; Ken G. Ryan (Cryobiology, 2024)

What makes a change agent in environmental conflict transformation? Evidence from rural France - Simon Calla; Lou Lécuyer; James R. A. Butler; Juliette C. Young (Biodiversity and Conservation, 2024)
Transformation of agriculture towards increased sustainability is needed to meet the challenge of declining biodiversity. Nevertheless, stakeholders’ differing perceptions of what sustainability should be, and the multiplicity of possible ways to achieve it can lead to conflictual situations, highlighting the importance of conflict transformation as part of the broader sustainability transformation. If conflict transformation needs to be addressed to prevent the status quo persisting, such processes also reveal the state of social relations and allow us to analyze how collective actions could lead to broader transformations. Using three case studies involving conflicts around pesticide use in the region Bourgogne Franche-Comté (France), we investigate the hypothesis that transformation processes require the engagement of change agents who are motivated and able to overcome barriers to change. Results from 55 in-depth interviews with stakeholders highlight that transformational change depends less on the capacities of a single individual, and more on the mobilization of a plurality of heterogeneous actors (especially farmers, local authorities, and the general public). These actors need to carry out a range of activities that occur with and for others and have an influence on others. According to interviewees, the actors need to engage others, encourage new initiatives, create spaces for knowledge exchanges, and go beyond boundaries. The effectiveness of change agents also depends on the existence of participatory and proactive processes to bring individuals together to create or capitalize on windows of opportunity.

Cryopreservation of diverse symbiodiniaceae species: fatty acid profiles, growth and photosynthetic performance - Joseph Kihika; Susanna Wood; Lesley Rhodes; Kirsty Smith; Matthew Miller; Xavier Pochon; Lucy Thompson; Juliette Butler; Clint Oakley; Ken Ryan (Cryobiology, 2023)

Addressing Marine and Coastal Governance Conflicts at the Interface of Multiple Sectors and Jurisdictions - Manuel Bellanger; Cameron Speir; Fabian Blanchard; Kate Brooks; James R. A. Butler; Scott Crosson; Robert Fonner; Sophie Gourguet; Daniel S. Holland; Sakari Kuikka; Bertrand Le Gallic; Rebecca Lent; et al. (Frontiers in Marine Science, 2020)

Less government intervention in biodiversity management: risks and opportunities - Juliette C. Young; James R. A. Butler; Andrew Jordan; Allan D. Watt (Biodiversity and Conservation, 2012)

TGF-β1 favors the development of fast type identity during soleus muscle regeneration - Philippe Noirez; Sandra Torres; José Cebrian; Onnik Agbulut; Juliette Peltzer; Gillian Butler-Browne; Dominique Daegelen; Isabelle Martelly; Angelica Keller; Arnaud Ferry (Journal of Muscle Research and Cell Motility, 2006)